2021
DOI: 10.1007/s12288-021-01411-2
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Indices and Their Kinetics Predict Mortality in Patients of Sepsis

Abstract: Platelet indices are inexpensive, easily accessible parameters and potentially useful prognostic indicators in sepsis. In this study we explore the differences in platelet indices and their kinetics between sepsis survivors and non-survivors. A retrospective cohort-study of 97 cases of culture-positive sepsis at a tertiary-care center in North India. Demographics, clinical and laboratory parameters at admission were assessed. Platelet count (PLT), mean-platelet-volume (MPV), platelet-distribution-width (PDW) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 34 publications
1
20
0
2
Order By: Relevance
“…Patients with septic shock evaluated in this study had high hematological failure, showing a positive correlation between thrombocytopenia and sepsis. Our results corroborate those of the study by Mangalesh et al [ 17 ] in which a high MPV and low platelet count were significantly associated with sepsis severity and mortality.…”
Section: Discussionsupporting
confidence: 93%
“…Patients with septic shock evaluated in this study had high hematological failure, showing a positive correlation between thrombocytopenia and sepsis. Our results corroborate those of the study by Mangalesh et al [ 17 ] in which a high MPV and low platelet count were significantly associated with sepsis severity and mortality.…”
Section: Discussionsupporting
confidence: 93%
“…[2][3][4][5][6] We have previously demonstrated the utility of NLR in various disease conditions including CAD. [6][7][8][9][10][11] In our analysis of NLR as a predictor of CAD severity rather than the diagnosis of CAD, we found that it was a significant predictor among both sexes.The authors 1 also show that low-density lipoprotein (LDL) and total cholesterol were not significant predictors of the presence of CAD in their population, which is an uncommon finding when compared with reports from Western populations. Likewise, as more data on NLR from different ethnicities are collated, more light will be shed on the ethnicity and sex-specific complex mechanisms behind CAD.The authors describe NLR as an effective risk marker for CAD among males, when compared with non-CAD patients, and report no significant results for female patients.…”
mentioning
confidence: 99%
“…Due to integrating both the neutrophil–lymphocyte ratio (NLR) and the monocyte–lymphocyte ratio (MLR) into one index, the SIRI should theoretically outperform both its components. The diagnostic and prognostic utility of the NLR and MLR has been confirmed previously in several disease conditions including cardiovascular diseases [ 2 , 3 ].…”
mentioning
confidence: 68%